Impact of parental lifestyle patterns in the preconception and pregnancy periods on childhood obesity - Lecorguillé, Marion; Schipper, Mireille C.; O’Donnell, Aisling; Aubert, Adrien M.; Tafflet, Muriel; Gassama, Malamine; Douglass, Alexander; Hébert, James R.; de Lauzon-Guillain, Blandine; Kelleher, Cecily; Charles, Marie-Aline; Phillips, Catherine M.; et al. (Frontiers in Nutrition, 2023)
Introduction High prevalence of overweight and obesity already observed in preschool children suggests the involvement of early-life risk factors. Preconception period and pregnancy are crucial windows for the implementation of child obesity prevention interventions with parental lifestyle factors as relevant targets. So far, most studies have evaluated their role separately, with only a few having investigated their potential synergistic effect on childhood obesity. Our objective was to investigate parental lifestyle patterns in the preconception and pregnancy periods and their association with the risk of child overweight after 5 years. Materials and methods We harmonized and interpreted results from four European mother-offspring cohorts participating in the EndObesity Consortium [EDEN, France; Elfe, France; Lifeways, Ireland; and Generation R, Netherlands] with data available for 1,900, 18,000, 1,100, and 9,500 families, respectively. Lifestyle factors were collected using questionnaires and included parental smoking, body mass index (BMI), gestational weight gain, diet, physical activity, and sedentary behavior. We applied principal component analyses to identify parental lifestyle patterns in preconception and pregnancy. Their association with risk of overweight (including obesity; OW-OB) and BMI z-scores between 5 and 12 years were assessed using cohort-specific multivariable logistic and linear and regression models (adjusted for potential confounders including parental age, education level, employment status, geographic origin, parity, and household income). Results Among the various lifestyle patterns derived in all cohorts, the two explaining the most variance were characterized by (1) “high parental smoking, low maternal diet quality (and high maternal sedentary behavior in some cohorts)” and, (2) “high parental BMI and low gestational weight gain.” Patterns characterized by high parental BMI, smoking, low diet quality or high sedentary lifestyle before or during pregnancy were associated with higher risk of OW-OB in children, and BMI z-score at any age, with consistent strengths of associations in the main cohorts, except for lifeways. Conclusion This project provides insight into how combined parental lifestyle factors in the preconception and pregnancy periods are associated with the future risk of child obesity. These findings are valuable to inform family-based and multi-behavioural child obesity prevention strategies in early life.